Digestible lysine levels in diets supplemented with ractopamine - Souza,Evelar de Oliveira (2011)
In order evaluate digestible lysine levels in diets supplemented with 20 ppm of ractopamine on the performance and carcass traits, 64 barrows with high genetic potential at finishing phase were allotted in a completely randomized block design with four digestible lysine levels (0.80, 0.90, 1.00, and 1.10%), eight replicates and two pigs per experimental unit. Initial body weight and pigs' kinship were used as criteria in the blocks formation. Diets were mainly composed of corn and soybean meal supplemented with minerals, vitamins and amino acids to meet pigs' nutritional requirements at the finishing phase, except for digestible lysine. No effect of digestible lysine levels was observed in animal performance. The digestible lysine intake increased linearly by increasing the levels of digestible lysine in the diets. Carcass traits were not influenced by the dietary levels of digestible lysine. The level of 0.80% of digestible lysine in diets supplemented with 20 ppm ractopamine meets the nutritional requirements of castrated male pigs during the finishing phase.